Optimizing Zinc Content Through Agronomic Bio-Fortification To Enhance Wheat Productivity - Javeria Muhammad Ahmad, Zaib Un Nisa, Muhammad Taqqi Abbas, Hafsa Farooq, Rimsha Ishtiaq (Migration Letters, 2022)
Zinc (Zn) is required for maintenance of different functions in plants and humans. Its deficiency leads to abnormal functioning and certain diseases. So, zinc should be taken in appropriate amount as part of daily diet. Majorly, countryside based poor populations consume cereals as major part of their diet which usually have poor nutritional quality due to less availability of micronutrients such as zinc (Zn), iron (Fe) and vitamins. Therefore, most people are suffering from hidden hunger in Pakistan. This experiment was planned to study the interaction of different Zn application methods with two contrasting genotypes of wheat with respect to growth, yield and Zn accumulation. The experiment was performed with two factors: first factor was two different wheat genotypes having different zinc uptake potential (Akbar-19 and Faisalabad-2008) and second factor was different application methods of zinc fertilizer. No zinc fertilizer was applied in control. Zinc applications was done via soil application (10 kg Zn ha-1), foliar application (1% w/v ZnSO4), seed coating (1.25 g Zn kg-1) and seed priming (0.5M ZnSO4). Results show that Akbar-19 had significantly higher plant height (93.74 cm) and spike length (11.30 cm) than Faisalabad-2008. However, Faisalabad-2008 exhibited higher 1000-grain weight (43.22 g), the number of tillers m-2 (524.50) and biological yield (15.47 t ha-1). Among Zn application methods, soil application method was better in terms of[1] number of tillers m-2 (555.31), 1000 grain weight (46.43 g), number of grains per spike (63.16), biological yield (16.40 t ha-1), and harvest index (33.67%). In terms of yield, soil application method provided the greatest grain yield (5.06 t ha-1), 16.85% higher than control method and Faisalabad-2008 provided the greatest grain yield (4.59 t ha-1), 7.24% higher than Akbar-19. While foliar application method provided the highest grain zinc contents (43.33 mg kg-1) which is 40.49% higher than control method and Akbar-19 provided highest grain zinc contents (35.34 mg kg-1) which is 3% higher than Faisalabad-2008. Soil application and Faisalabad-2008 can provide the optimal yield and productivity while foliar application in Akbar-19 can provide optimal grain zinc contents.